2018
DOI: 10.1556/2006.7.2018.35
|View full text |Cite
|
Sign up to set email alerts
|

Expression of NMDA receptor subunits in human blood lymphocytes: A peripheral biomarker in online computer game addiction

Abstract: Background and aimsRepeated performance of some behaviors such as playing computer games could result in addiction. The NMDA receptor is critically involved in the development of behavioral and drug addictions. It has been claimed that the expression level of neurotransmitter receptors in the brain may be reflected in peripheral blood lymphocytes (PBLs).MethodsHere, using a real-time PCR method, we have investigated the mRNA expression of GluN2A, GluN2D, GluN3A, and GluN3B subunits of the NMDA receptor in PBLs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 73 publications
(91 reference statements)
0
8
0
Order By: Relevance
“…Studies have shown that 23.3, 26.3, and 21.7% of patients with PIU suffer from anxiety disorder, depression, and ADHD, respectively (6). Many researchers have confirmed the aetiological mechanism of PIU, and considerable evidence is available regarding changes in the central and peripheral nervous systems in patients with PIU (7,8). However, the exact physiopathological mechanism of PIU remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that 23.3, 26.3, and 21.7% of patients with PIU suffer from anxiety disorder, depression, and ADHD, respectively (6). Many researchers have confirmed the aetiological mechanism of PIU, and considerable evidence is available regarding changes in the central and peripheral nervous systems in patients with PIU (7,8). However, the exact physiopathological mechanism of PIU remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Computer games as an environmental factor cause gene expression, hormonal, neurological, and behavioral changes in CNS. According to the literature, environmental factors may adversely affect the neurological system, normal secretion of hormones, and even gene expression of N-methyl-D-aspartate (NMDA) receptors ( Sadat-Shirazi et al, 2018 ; Tekieh et al, 2017 ). The gene expression of NMDA receptors plays a key role in developing cognitive abilities such as attention, concentration, memory, and learning among animals and human beings.…”
Section: Discussionmentioning
confidence: 99%
“…The gene expression of NMDA receptors plays a key role in developing cognitive abilities such as attention, concentration, memory, and learning among animals and human beings. Environmental factors in urban areas, such as electromagnetic fields, electric fields, and even computer games, act as activators or inhibitors of gene expression of NMDA receptors ( Aliyari et al, 2019 ; Kazemi et al, 2018 ; Sadat-Shirazi et al, 2018 ). Several studies have shown that computer game addiction would alter the expression level of NMDA receptors ( Sadat-Shirazi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioural addictions are disorders analogous to substance addiction, in which there is a behavioural core based on repeated performances. The analysis of mRNA levels of different NMDAR subunits in human blood lymphocytes surprisingly revealed a reduction in GRIN3A mRNA levels in computer game addicts (Sadat-Shirazi et al 2018). Dysregulated Grin3a expression has also been observed during transgenerational transmission of hedonistic and addictive behaviours such as increased preference of palatable foods (Sarker et al 2019).…”
Section: Addiction and Hedonistic Behaviourmentioning
confidence: 99%